ABFAB. Attachment to the breast and family attitudes to breastfeeding. The effect of breastfeeding education in the middle of pregnancy on the initiation and duration of breastfeeding: a randomised controlled trial [ISRCTN21556494] - Waldenström Ulla; Harris Heather; Beanland Christine; Lumley Judith; McLachlan Helen; Forster Della; Earl Diane; Dyson Kaye (BMC Pregnancy and Childbirth, 2003)
Abstract Background It has proven difficult to reach World Health Organization (WHO) recommendations that infants be exclusively breastfed from birth to six months of age <abbrgrp>12</abbrgrp>, yet there is limited knowledge about interventions that are effective in increasing breastfeeding initiation and duration. Particularly lacking is evidence about how to maintain breastfeeding rates in countries which already have a high initiation of breastfeeding. This study aims to determine whether mid-pregnancy breastfeeding education, with a focus on either attitudes to breastfeeding or on technical aspects of breastfeeding, has an effect on rates of breastfeeding initiation and duration. Secondary aims of the study are to: explore what factors might affect the duration of breastfeeding and evaluate the interventions from the participant and childbirth facilitator perspectives. Methods/Design A randomised controlled trial (RCT) design will be used. Women having their first baby, and planning to give birth as public patients at the Royal Women's Hospital (RWH), Melbourne, will be approached at 18–20 weeks of pregnancy and invited to participate in the study. Participants will be randomly allocated to a control group or one of two group interventions: a previously designed and trialled tool to teach practical aspects of breastfeeding or an exploration of family attitudes to breastfeeding. The latter was developed and piloted by the investigators in conjunction with the group facilitators, prior to trial commencement. The interventions are planned to take place at 20–25 weeks. Data will be collected by questionnaire at recruitment, at interview in hospital after the birth and by telephone interview six months later. Medical/obstetric outcomes will be obtained from the medical record. The sample size (972) was calculated to identify an increase in breastfeeding initiation from 75 to 85% and an increase from 40 to 50% in breastfeeding at six months.